Metal foil for screen printing plate and screen printing plate including same - TAKASHI KOBORI; KOICHI MIYATA; TATSUAKI SHINODA (2017)
The invention provides a screen printing plate capable of forming a highly reliable printed matter with less disconnection and a metal foil used therefor. A metal foil used for a screen printing plate for screen printing has a plurality of openings arranged along one direction, and a rib shape between adjacent openings and openings is formed in the one direction and provided with a first corner portion and a second corner portion on one side and the other side of the metal foil; in a cross section perpendicular to the surface of the metal foil and parallel to the one direction, an angle formed by the second corner portion is set larger than the angle formed by the first corner portion. 本发明提供种能够形成断线少且可靠性高的印刷物的丝网印刷版以及该丝网印刷版所使用的金属箔。在丝网印刷用的丝网印刷版所使用的金属箔中，多个开口部沿着方向设置，相邻的开口部与开口部之间的肋形状在所述方向的方侧和另方侧具有第角部和第二角部，在与所述金属箔的表面垂直且与所述方向平行的剖面中，所述第二角部所成的角度设定为大于所述第角部所成的角度。